2021
DOI: 10.3390/jpm11060545
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin Combined with Rehabilitation Enhances Motor Recovery and Prevents Neural Network Degeneration in Ischemic Stroke Patients with Severe Motor Deficits

Abstract: The objective of this study was to evaluate whether Cerebrolysin combined with rehabilitation therapy supports additional motor recovery in stroke patients with severe motor impairment. This study analyzed the combined data from the two phase IV prospective, multicenter, randomized, double-blind, placebo-controlled trials. Stroke patients were included within seven days after stroke onset and were randomized to receive a 21-day treatment course of either Cerebrolysin or placebo with standardized rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Cerebrolysin is already contributing to the pharmacological armamentarium that clinicians have at their disposal in many countries worldwide [ 9 , 10 , 13 ]. Despite the prolific literature that has been published on the efficacy and safety of the add-on intervention for post-stroke neurorehabilitation, some limitations of clinical studies (e.g., small sample sizes) warrant additional investigation via large, high-quality confirmatory trials, as well as clinical and cost-effectiveness studies [ 4 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Improving this body of evidence in the future will impact current clinical guideline recommendations for Cerebrolysin after ischemic stroke, likely clarifying divergent opinions on this topic [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebrolysin is already contributing to the pharmacological armamentarium that clinicians have at their disposal in many countries worldwide [ 9 , 10 , 13 ]. Despite the prolific literature that has been published on the efficacy and safety of the add-on intervention for post-stroke neurorehabilitation, some limitations of clinical studies (e.g., small sample sizes) warrant additional investigation via large, high-quality confirmatory trials, as well as clinical and cost-effectiveness studies [ 4 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Improving this body of evidence in the future will impact current clinical guideline recommendations for Cerebrolysin after ischemic stroke, likely clarifying divergent opinions on this topic [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al focused on the combination of Cerebrolysin with standardized rehabilitation therapy. The results showed that in individuals with severe motor impairment caused by acute ischemic stroke, conventional rehabilitation therapy combined with Cerebrolysin delivers extra benefits to conventional rehabilitation therapy alone in motor recovery [ 36 ]. An earlier study by Chang et al (which used for the first-time neuroimaging for motor network plasticity evaluation when administering Cerebrolysin) revealed a positive influence of Cerebrolysin on cerebral tissue related to motor function, but no significant difference was found between the two groups [ 37 ].…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In order to apply individual treatment, research on the mechanism of action of a new treatment method is also essential. Lee et al [ 18 ] reported the change of cortical activity by high-definition transcranial direct current stimulation (HD-tDCS) and Chang et al [ 19 ] showed the potential mechanisms of Cerebrolysin for improving motor function in stroke patients [ 19 ]. Recent studies suggested appropriate indications for stem cell therapy [ 20 ] and transcranial direct current stimulation (tDCS) [ 21 ].…”
mentioning
confidence: 99%
“…This article is meaningful in that genetic factors might be considered in stroke treatment. These reports [ 18 , 19 , 20 , 21 ] might be used as references for personalized stroke therapy in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation